2017
DOI: 10.1108/hff-03-2016-0120
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of heat transfer in a square channel by roughened surfaces in rib-elements and turbulent flow manipulation

Abstract: Purpose The purpose of this paper is to augment heat transfer rates of traditional rib-elements with minimal pressure drop penalties. Design/methodology/approach The novel geometries in the present research are conventional cylindrical ribs with rounded transitions to the adjacent flat surfaces and with modifications at their bases. All turbulent fluid flow and heat transfer results are presented using computation fluid dynamics with a validated v2f turbulence closure model. Turbulent flow characteristics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Their predictions indicated that this twisted implant could improve the thermal convection performance by 1.8-4.5 times. Liu et al (2017) applied a V2F turbulence model to the analysis of turbulent thermal flow and the enhancement of thermal performance in various channels equipped with ribbed inserts. Wu and Perng (2005) combined the large eddy simulation turbulence model with the semi-implicit method for pressure-linked equation (SIMPLE-C) algorithm to simulate the turbulent thermal flow field and then evaluated the heat transfer promotion of a block-heated channel.…”
Section: Introductionmentioning
confidence: 99%
“…Their predictions indicated that this twisted implant could improve the thermal convection performance by 1.8-4.5 times. Liu et al (2017) applied a V2F turbulence model to the analysis of turbulent thermal flow and the enhancement of thermal performance in various channels equipped with ribbed inserts. Wu and Perng (2005) combined the large eddy simulation turbulence model with the semi-implicit method for pressure-linked equation (SIMPLE-C) algorithm to simulate the turbulent thermal flow field and then evaluated the heat transfer promotion of a block-heated channel.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the wave-shaped triangular ribs generated vortices to disorder the thermal boundary layer effectively to raise heat transfer rate. Liu et al (2017) explored the heat and fluid flow in square passages with novel ribbed structures via computational analysis. Their findings indicated that rounded transition cylindrical rib had thermal performance better than the traditional rib under considering pressure loss.…”
Section: Introductionmentioning
confidence: 99%
“…This was due to larger strength of cross flow induced by the jet in the downstream region. Liu et al (2017) carried out a computational study of the effect on ribs in a square channel. Among all rib geometries, the round transition cylindrical ribs gave the highest heat transfer.…”
Section: Introductionmentioning
confidence: 99%